Which expression is NOT equivalent to 24 + 6x?
A. 2(3x + 12)
B. 28 + 4x – 4 + 2x
C. 5x + 7 + x + 17
D. 3(8 + 3x)

Respuesta :

Answer:

D

the answer is D because when you multiply 3(8 + 3x), it will give you 24+9x

3(8 + 3x)  is not equivalent to 24 + 6x.

Option D expression is not equivalent to 24 + 6x.

What is an expression?

An expression or algebraic expression is any mathematical statement which consists of numbers, variables and an arithmetic operation between them.

According to the question

Expression is NOT equivalent to 24 + 6x

A . 2(3x + 12)

= 2(3x) + 2(12)

= 6x  + 24

= 24 + 6x

B. 28 + 4x – 4 + 2x

= (28 - 4) + (4x + 2x)

= 24 + 6x

C. 5x + 7 + x + 17

= (5x + x) + (7 + 17)

= 6x + 24

= 24 + 6x

D. 3(8 + 3x)

= 3(8x) + 3(3x)

= 24 + 9x

Hence, Option D is not equivalent to 24 + 6x.

3(8 + 3x)  is not equivalent to 24 + 6x.

Find out more information about expression here

https://brainly.com/question/19131200

#SPJ2

ACCESS MORE